## Solving the Quadratic Equation (x+3)(x+4) = 0

This article will guide you through solving the quadratic equation (x+3)(x+4) = 0 and understanding the process of converting it to standard form.

### Understanding the Equation

The equation (x+3)(x+4) = 0 is already factored. This means it's in a form that makes it easy to find the solutions.

**Key Concept:** For a product of two or more factors to equal zero, at least one of the factors must be zero.

### Solving for x

To find the solutions, we set each factor equal to zero:

**x + 3 = 0**- Subtract 3 from both sides:
**x = -3**

- Subtract 3 from both sides:
**x + 4 = 0**- Subtract 4 from both sides:
**x = -4**

- Subtract 4 from both sides:

Therefore, the solutions to the quadratic equation (x+3)(x+4) = 0 are **x = -3** and **x = -4**.

### Standard Form of a Quadratic Equation

The standard form of a quadratic equation is **ax² + bx + c = 0**, where a, b, and c are constants and a ≠ 0.

To convert the given equation to standard form, we need to expand the product:

**(x+3)(x+4) = 0**

**x² + 4x + 3x + 12 = 0****x² + 7x + 12 = 0**

Now the equation is in standard form: **x² + 7x + 12 = 0**.

### Conclusion

We have successfully solved the quadratic equation (x+3)(x+4) = 0 by using the factored form to find the solutions: x = -3 and x = -4. We also converted the equation to standard form: x² + 7x + 12 = 0. This process demonstrates the relationship between factored and standard forms of quadratic equations and how they can be used to solve for the roots.